The Pragmatic Approach in Analyzing Qur'anic Dialogues: Between Advocates and Critics - Muhammad Hashimee; Azlan Shaiful Baharum; Abdul Azim Mohamad Isa Mohamad Isa; Khalid Ludin (2025)
Non Index Publication (Tier 4)